Smartphone Addiction Reviewed from Big Five Personality in College Students - Bhayangkara, Noer Ichsan; Lerik, Mariana Dinah Ch; Benu, Juliana Marlin Y (Universitas Nusa Cendana, 2024)
Smartphones have many advantages, but can also cause detrimental effects, namely addiction. Smartphone addiction is a behavior of dependence on smartphones which can cause various problems in students' lives. Personality traits are closely related to addictive behavior. The personality theory most used to uncover addiction is the Big Five Personality. This research aims to determine the relationship between the Big Five personality dimensions and smartphone addiction in students. This research is a quantitative correlation research. The sample in this study amounted to 325 respondents obtained using purposive sampling. Data was taken using the SAS (Smartphone Addiction Scale) and BFI (Big Five Inventory) scales. The analysis technique uses the Spearman rank test. The results show that the dimensions of conscientiousness (0.001<0.05), extraversion (0.006<0.05), and neuroticism (0.001<0.05) have a significant relationship with smartphone addiction while Openness to experience (0.175>0.05) and agreeableness (0.367>0.05) doesn't have a significant relationship with smartphone addiction in students.